Adaptation and Validation of Standardized Aphasia Tests in Different Languages: Lessons from the Boston Diagnostic Aphasia Examination–Short Form in Greek - Kyrana Tsapkini; Christina Helen Vlahou; Costantin Potagas (Behavioural Neurology)
The aim of the current study was to adapt the Boston Diagnostic Aphasia Examination – Short Form (BDAE-SF) [1] to the Greek language and culture, determine the influence of demographic variables on performance and in particular the effects of age and education, develop normative data, and examine the discriminative validity of the test for acute stroke patients. A sample of 129 community healthy adults participated in the study (66 women), covering a broad range of ages and education levels so as to maximize representation of the Greek population and be able to examine the effects of age and education in language performance. Regression models showed that, overall, younger and more educated individuals presented higher performance on several subtests. Normative data for the Greek population are presented in percentile tables. Neurological patients' performance was compared to that of the neurologically intact population using Wilcoxon's rank sum test and for the most part was found to be significantly inferior, indicating good discriminant validity of the test. Qualitative errors of patients diagnosed with aphasia on the test are presented, and limitations and generalizable strengths of this adaptation are discussed.